Pelatihan Menulis Konten Media Online pada Pelaku UMKM Desa Galengdowo, Kecamatan Wonosalam, Kabupaten Jombang - Bagus Cahyo Shah Adhi Pradana; Mohammad Insan Romadhan (Universitas Mathla'ul Anwar Banten, 2020)
TRAINING OF ONLINE MEDIA CONTENT WRITING FOR SMES GALENGDOWO VILLAGE, WONOSALAM DISTRICT, JOMBANG REGENCY. Galengdowo is a village in Wonosalam District, Jombang Regency, East Java. Galengdowo Village consists of 5 hamlets namely Wates, Sanggar, Plumpung, Galengdowo, and Pangajaran Hamlet. Galengdowo Village is located on a plateau in the southeast of Jombang City on the slopes of Mount Anjasmoro. Lack of publication on the internet makes tourism potential and the results of its natural wealth less known by the public. Publication activities can be done through regular web content updates and village branding on social media such as Facebook and Instagram. The purpose of the Galengdowo.com website content writing training is as a means of promotion, publication, and introduction of MSME products to potential consumers through online media . In the community service program with training activities to create online media content on the SMEs of Galengdowo Village, Wonosalam, Jombang can be said to be successful. This can be seen from the increase in understanding of SMEs involved in the process of making online media content.